Strengthening digital ecosystem for SMEs through readiness to change and agile leadership - Hasan Abdul Rozak; Ardian Adhiatma; Ika Rosyada Fitriati (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
Purpose: This study aims to describe and analyze the relationship between readiness to change and agile leadership on the dynamic capabilities of SMEs. Furthermore, this study also examines the effect of dynamic capabilities in strengthening the digital ecosystem of SMEs.Design/methodology/approach: The data used in the study are collected from 250 SMEs through structured questionnaires. This study analyzes three hypotheses using structural equation modeling.Findings: The results of the study show that readiness to change and agile leadership can improve the dynamic capabilities of SMEs. The improved dynamic capabilities of SMEs are proven to be able to strengthen the digital ecosystem in SMEs. The results of this study are expected to contribute to SMEs in strengthening the growth of the digital economy in Indonesia.Research limitations/implications: This research has several limitation aspects, the research design is cross-sectional, and the research design cannot ensure that the causal relationship is specified in the hypothesis; in fact, the results tend to be consistent with theoretical reasoning. This study analyzes dynamic capabilities, a more specific approach may be needed to be able to fully utilize each process for the realization of a digital ecosystem. Another limitation, this study only examines the direct effect between a penchant for change and agile leadership on the capabilities of SMEs. Then test the direct influence between dynamic capabilities on the realization of a digital ecosystem.Practical Implications: The implication of the results of this research for management is as a literature on efforts to strengthen the digital ecosystem for SMEs through dynamic capabilities formed fro readiness to change and agile leadership. SME entrepreneurs must realize that change is a necessity along with the development of society and technology so that readiness to change becomes veri important. Besides, SME entrepreneurs are also required to have an agile leadership spirit so that they can guide and influence their team in achieving targets and solving problems properly.Originality/value: This study focuses on change readiness and agile leadership in relation to the dynamic capabilities of SMEs that can ultimately shape digital ecosystems. the results of this study provide additional empirical evidence for areas of research where there are few studies exist.